Occupational stress and its associated factors among academician in northern Malaysian universities - Omar, Mariani (2018)
The commonness of occupational stress among academician is increasing in developed and developing countries.The job is not only to teach, but also involve in doing research, publications, consultation and administrative work. This study aims to assess the commonness of occupational stress among academic staff in in Northern Malaysian universities and to investigate the association and correlation between stress and job factors which are self-administered and occupational stress, physical health; general health and use of medication; occupational stress index; depression, anxiety and Stress and stress sources.Three Northern Malaysian universities were selected randomly. A cross-sectional study was conducted and the respondents were recruited by using a randomized stratified sampling method.A total of 400 self-administered and validated Occupational Stress Scale (OSS); Physical Health Questionnaire (PHQ); General Health Questionnaire (GHQ) and use of medication; Occupational Stress Index (OSI); Depression, Anxiety and Stress Scale-21 (DASS-21) and Stress Sources Questionnaires (SSQ) will be distributed among academic staff.Continued hours of working and high workload and responsibility determine job stress status among academic staff.It is recommended that the management of the university plan and implement job stress prevention and management programs emphasizing on time management and working strategies to improve the situation.The study recommended for the importance of managing the various factors associated with stress and providing recreational program to promote their health.